2010
DOI: 10.1007/s00520-010-0933-7
|View full text |Cite
|
Sign up to set email alerts
|

The initial development of an instrument to assess the psychosocial needs and unmet needs of young people who have a parent with cancer: piloting the offspring cancer needs instrument (OCNI)

Abstract: Young people (aged 12-24 years) who have a parent with cancer report a complex array of needs, many of which go unmet. The preliminary findings reported may be used to inform service providers in the development and evaluation of need-based programs to redress these unmet needs and thus ameliorate the effects of parental cancer. Services addressing information and school-based interventions are particularly pertinent given these current results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 27 publications
4
39
0
Order By: Relevance
“…Parents were their major source of trust, safety, and comfort. Our findings partly confirm earlier studies concerning different kinds of difficulties at school (Su & Ryan-Wenger, 2007;Patterson et al, 2011), but school was also an important source of comfort and support. Maynard et al (2013) identified actions that parents can take to increase feelings of safety and support, including being available, inviting their children to talk, and spending quality time together.…”
Section: Discussionsupporting
confidence: 91%
“…Parents were their major source of trust, safety, and comfort. Our findings partly confirm earlier studies concerning different kinds of difficulties at school (Su & Ryan-Wenger, 2007;Patterson et al, 2011), but school was also an important source of comfort and support. Maynard et al (2013) identified actions that parents can take to increase feelings of safety and support, including being available, inviting their children to talk, and spending quality time together.…”
Section: Discussionsupporting
confidence: 91%
“…This in turn may impair personal development resulting in high levels of emotional and psychological distress . It was not surprising to see a strong association between distress levels and unmet needs, which has been reported by others …”
Section: Discussionmentioning
confidence: 63%
“…Each offspring was given password‐protected access to a study‐specific website. Participants recorded demographic data and completed the Kessler‐10 questionnaire (K10) and the Offspring Cancer Needs Instrument (OCNI) . The K10 is a validated 10‐item questionnaire, which measures psychological distress experienced in the preceding 4 weeks (Data S1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…books was high. This reflects the finding that information needs are high among AYAs affected by cancer (Clinton-McHarg et al, 2012;Patterson, Millar, Desille, & McDonald, 2012;Patterson, Millar, & Visser, 2011;Patterson, Pearce, & Slawitschka, 2011). In particular, the young people felt that the design and the ease of use of the book were excellent.…”
Section: Expectations and Satisfactionmentioning
confidence: 70%